PENGARUH LITERASI KEUANGAN, TOLERANSI RISIKO DAN OVERCONFIDENCE TERHADAP KEPUTUSAN PEMBELIAN CRYPTOCURRENCY - Andreas, Jose; kiky, andreas (Publika Citra Media, 2025)
Cryptocurrency is a digital asset that has captured the attention of traders due to its high volatility, offering the potential for significant returns. This study contributes to behavioral finance by providing insights into psychological and cognitive factors that influence cryptocurrency purchasing decisions, as well as offering practical guidance for novice traders to reduce impulsive behavior and enhance their financial literacy. The findings reveal that financial literacy has a significant positive impact on purchasing decisions, emphasizing the importance of financial understanding in making intelligent investment choices. Risk tolerance also shows a significant positive influence, illustrating that individuals with a high tolerance for risk are more inclined to invest in highly volatile assets like cryptocurrency. Overconfidence demonstrates a significant positive effect on purchasing decisions, reflecting a psychological bias where individuals often overestimate their knowledge and abilities. This study enriches behavioral finance by deepening the understanding of psychological and cognitive influences on cryptocurrency purchasing decisions while providing actionable advice for beginner traders to improve their decision-making and financial acumen.